Implementation of Early Childhood Multicultural Education in Increasing Tolerance - Agustina Tania; Wahyuda Dwi Handoko; Chlaudya Wihellmia; Maria Sisilia (Civiliza Publishing, Indonesia., 2025)
Multicultural education is an important approach in building tolerance from an early age, especially amidst the socio-cultural diversity of Indonesian society. Early childhood is in a period of rapid development in the social-emotional aspect, so it is necessary to provide stimulation through learning activities that respect differences, foster empathy, and encourage positive interactions between children with diverse religions and backgrounds. This study aims to analyze the implementation of multicultural education in increasing tolerance in early childhood at Santa Bernadeth Kindergarten. The study used a descriptive qualitative method with observation, interview, and documentation techniques. The results showed that multicultural education was implemented through contextual learning activities, the use of media based on religious and cultural diversity, inclusive habits, and social interaction practices that emphasize the value of mutual respect. Teachers have a central role as facilitators and role models in building tolerant behavior, while the school environment creates a culture that supports diversity. This study concludes that the consistent and planned implementation of multicultural education can increase empathy, cooperative skills, and acceptance of children's differences. These findings provide an important contribution to the development of tolerance learning models in schools.